SEARCH OF THE TRUTH IN STANDARD CONFUSION CRIMINAL AND EXECUTIVE RIGHT - Богатирьова, Ольга Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: establishment of correctness of the law-making equipment by definition of the central executive authority in the sphere of execution of criminal penalties and a probation. Methods: set of the general and special methods of scientific knowledge – terminological, functional, system and structural, logiko-standard. Results: own image of definition of the central executive authority in the sphere of execution of criminal penalties and a probation is formulated, the expediency of recognition of the Public criminal and executive service of Ukraine by him is proved, but not the Ministries of Justice of Ukraine, the place of Administration of DKVS of Ukraine as her central office is characterized, distribution of competence between subjects of criminal and executive policy – the Ministry of Justice of Ukraine and the Public criminal and executive service of Ukraine is opened, established a number of collisions in the criminal and executive legislation, ways of their elimination are offered. Discussion: introduction of amendments to the legislation on the matter.